2009
DOI: 10.1055/s-0029-1211266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of catecholamine depletion and denervation on neuropeptide Y(NPY) and tyrosine-hydroxylase (TH) mRNA levels in rat sympathetic ganglia

Abstract: Neuropeptide Y (NPY) and noradrenaline (NA) are synthesized and stored in sympathetic nerves and concomitantly released in response to appropriate stimuli. The two substances have been reported to interact on various levels: postjunctionally, by mutually potentiating their vasoconstrictor effects, prejunctionally, by inhibiting each other's release. The possibility of an interaction on the levels of their synthesis was investigated in this study. Specific cDNA probes were used for the measurement of the steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous studies showed that NPY gene expression is sensitive to both pharmacologic and physiological stimuli (20,26,63,72). IH-induced increase in preproNPY mRNA in the rat AM is reminiscent of a similar augmentation of pre-proNPY mRNA elicited by immobilization stress and pharmacologic interventions in rat sympathetic neurons (21,47) and the sympatho-adrenal system (26,38,63). Stress, in addition to stimulating neuronal input to the AM, increases circulating glucocorticoids.…”
Section: Ih and Prepronpy Mrna Expressionmentioning
confidence: 91%
“…Previous studies showed that NPY gene expression is sensitive to both pharmacologic and physiological stimuli (20,26,63,72). IH-induced increase in preproNPY mRNA in the rat AM is reminiscent of a similar augmentation of pre-proNPY mRNA elicited by immobilization stress and pharmacologic interventions in rat sympathetic neurons (21,47) and the sympatho-adrenal system (26,38,63). Stress, in addition to stimulating neuronal input to the AM, increases circulating glucocorticoids.…”
Section: Ih and Prepronpy Mrna Expressionmentioning
confidence: 91%